Metal-Free Heptazine-Based Porous Polymeric Network as Highly Efficient Catalyst for CO2 Capture and Conversion - Sharma, Neha; Ugale, Bharat; Kumar, Sunil; Kailasam, Kamalakannan (Frontiers in Chemistry, 2021)
Capture and catalytic conversion of CO2 into value-added chemicals is a promising and sustainable approach to tackle the global warming and energy crisis. The nitrogen-rich porous organic polymers (POPs) are excellent materials for CO2 capture and separation. Herein, we present a nitrogen-rich heptazine based microporous polymers for the cycloaddition reaction of CO2 with epoxides in the absence of metal and solvent. HMP-TAPA being rich in nitrogen site showed high CO2 uptake 106.7 mg/g with IAST selectivity of 30.79 towards CO2 over N2. Further, HMP-TAPA showed high chemical and water stability without loss of any structural integrity. Besides CO2 sorption, catalytic activity of HMP-TAPA was checked for cycloaddition of CO2 and terminal epoxides resulting in cyclic carbonate with high conversion (98%). They showed remarkable recyclability upto 5 cycles without loss of activity. Overall, this work represents a rare demonstration of rational design of a POPs (HMP-TAPA) for multi-applications.